Desperately seeking evidence: the recovered memory debate - Memon, Amina (Legal and criminological psychology, 1997)
Purpose. The debate concerning the recovery of repressed memories of childhood sexual abuse (CSA) is one with which academics and professionals are becoming increasingly familiar. This paper asks whether or not recovered memories require special psychological mechanisms to explain as this has implications if legal proceedings are initiated on the basis of that recovered memory. Method. The following areas are deemed relevant when evaluating evidence based upon a recovered memory: (i) the effects of trauma on memory (an influence on memory at the encoding stage); (ii) how memory can be aided and distorted (an influence on memory at the retrieval stage); and (iii) factors likely to influence jury decisions concerning recovered memories. Results. Cases documenting the veracity of recovered memories are few and far between. On the contrary there is sufficient evidence to be concerned about the accuracy of recovered memories in the legal context. Conclusions. Further research is needed on the conditions under which false recollections may occur and how these may be prevented.